Advances in industrial and labor relations. Vol. 20 - Lewin, David, 1943-; Gollan, Paul J. (Advances in industrial and labor relations., 2012)
Volume 20 of Advances in Industrial and Labor Relations (AILR) contains seven papers that deal with important aspects of employment relationships in a variety of industries, countries and research contexts. The first three papers, each of which analyzes the effects of an exogenous variable (e.g., fiscal adversity, globalization, and new technology, respectively) on labor-management relations, have specific industry/sector settings, namely, pubic schools (primary education), civil aviation and nursing homes (health care), respectively. The first and third of these papers are set in the U.S., the second in Britain. The next four papers, each of which analyzes the effects of enacted or contemplated legislation on specific aspects of labor-management relations and workplace dispute resolution, are set in Canada, Australia, New Zealand and the U.S., respectively. The research designs featured in these papers include quasi-experimental, case studies, interviews, surveys and simultaneous equation modeling.